Food Security and Agroecology: perceptions of students and teachers in the area of Natural Sciences in a rural school context (Research, Society and Development, 2022)
The issue of food security and food production in order to guarantee the supply of the population in quantity and quality of nutrients, respecting the cultures of different peoples and producing them without environmental degradation, constitutes one of the great contemporary challenges, from which we propose to think of Agroecology as one of the viable ways to do so, and therefore we understand the presence of this theme in school as important. In this sense, this work seeks to analyze the concepts on Agroecology, Food Security and the issue of food production, from students of the third year of High School (EM) and teachers in the area of Natural Sciences, from a public school in state network of Rio Grande do Sul, in a rural school context. The instruments used in the research were interviews with teachers and the application of questionnaires to teachers and students. Qualitative data were treated from Discursive Textual Analysis (DTA), from which the categories of analysis emerged: understandings of food security, understandings of agroecology and pedagogical practices involving food production and food. The quantitative data resulting from the questionnaires generated the statistics presented in the form of graphs during the work. The results indicated that the conceptions of students and teachers converged towards an understanding of the importance of the proposed theme, and the feasibility of these discussions within the scope of classes in the area of natural sciences.